Peran Kepemimpinan Kepala Desa dalam Membangun Sumber Daya Manusia - Sri Mulyeni; Santi Santi; Lien Nurliah; Imas Siti Masitoh; Vip Paramarta (Jurnal Bintang Manajemen, 2023)
The leadership of the Citatah Village Head plays an important role in developing the community of Citatah Village, Cipatat District West Bandung, the village head is the main key in driving human resource developmentin the village environment. Through data collected through interviews, observation and documentation analysis involving village heads, village officials and village communities. The author can provide an overview of the Citatah Village Head, namely that the village head is able to play an active role in human resource development programs, building awareness and the spirit of community participation through effective communication and collaboration with the local community. The transformational leadership used by the village head makes working relationship and relations with the community more harmonious. The discipline applied by the village head can be accepted by every village official. However village officials have hopes of providing rewards from the village head for optimal performance carried out by village officials both in terms of service performance and development in the field. It is hoped that the provision of these rewards con further motivate the performance of existing village officials.